Incedental Cancer of Prostate Among Patienst Undergoimg Transurethral Resection of Prostate aged more than 50 Years - Rehan Akhtar, Muhammad Rahil Khan, Riyasat Ahmed Memon, Yusra Shafquat, Abdul Aziz Shaikh, Suresh Kumar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the incidental cancer of prostate among patienst undergoimg transurethral resection of prostate aged more than 60 years at tertiary care Hospital Subjects and Methods: This cross-sectional asutyd was done at pathology daerpatemnt of LUMHS from January 2019 to December 2020. Satudy was done after atking ethical approval fron ethical review commetee of LUMHS Jamshoro. TURP specimens underwent overnight processing after being fixed ino 10% neutral buffered formalin. Each block had a single section taken from it that was stained with hematoxylin and eosin and inspected histologically. On the glass slides, all foci were marked, and the tumour volume was calculated as a visual representation of the tumor’s percentage of the specimen’s total surface area. According on the 2005 International Association of Urological Pathol (ISUP) consensus recommendations, Gleason scoring was performed. With immunoperoxidase staining, small tumour foci were confirmed. pT1a disease was defined as incidental tumor in 5% of TURP specimens. pT1b disease was defined as incidental tumor in > 5% of TURP specimens. All the data was collected via suyd profoema. SPSS version 26 was used for the data analysis. Results: A toat of 800 cases were studied the incidence of prostate carcinoma was estimated 39.25%. mean age of the patients was 66.95+9.37 years. Most of the cases had, tumor grade II to V as 18.3%, 18.3%, 17.0% and 36.9% respectively. As per estimated tumor invasion, most of the cases had tumor invasion was >25% as 22.8% ahd tumor invesion 26-50%, 27.6% and 51-75% and 30.1% had 76-100%. Perineural invasion was observed in 42.3%of the cases and lymphovascular invasion was only in 3.2% of the acses. Conclusion: The incidence of prostate carcinoma was observed to the highly frrequenct as estimated 39.25% and most of the cases had, tumor grade II to V. Keywords: Prostate, incidental cancer, stages